DESIGNING LESSON ACTIVITIES THROUGH MALUKU FOLKLORE FOR CHARACTER EDUCATION - Mansye Sekewael; Frida Pentury; Welma Noija (International Conference on Education and Language (ICEL), 2016)
The teaching and learning process at school has notbeen able to shape the graduates as whole persons who reflect the character and the culture of thenation. The education process still emphasizes and focuses its outcome on the cognitive aspects. Meanwhile, the affective aspects of the learners which will become the strong basis to live in thecommunity have not been developed optimally. Therefore, characters education must be developed in school. One of the best ways is by introducing folklore in EFL class.In introducing local folktale (more specific to Maluku folktale) for characters education can serve potential materials for teaching character education as Maluku folklore not only reflect Maluku culture but also contain values and moral lessons. This article tries to explore more detail the value in “Harman Pardidu” story. This story is broaden of characters education which are implemented in lesson activities as a design for the EFL Teachers who wants to create their classes become fun, enjoyable, non-preachy and effective. Relating to this, language teachers are recommended to capitalize on the use of folklore by creatively designing activities relevant to character educations as well as adapting them in accordance with the students‟ level of proficiency”.